MODERN APPROACHES TO ASSESSMENT OF THE BREAST-FEEDING BY THE EXAMPLE OF THE CHECHEN REPUBLIC AND THE REPUBLIC OF INGUSHETIA - L. V. Abol'yan; P. M. Evloeva; E. I. Barteneva ("Paediatrician" Publishers LLC, 2013)
In order of assess the results of introduction of the programs aimed at maintenance and support of the breast-feeding it is necessary to use uniform indicators, which guarantee consistency, reliability and comparability of the data. Aim: to perform complex medical and social assessment of the prevalence and duration of the breast-feeding by the example of the Chechen Republic (CR) and the Republic of Ingushetia (RI). Patients and methods: mothers of children aged 12-36 months old were interviewed (n =2200). Statistical analysis was performed with the means of the software «SPSS.17». Results: the mean duration of the breast-feeding in the CR was 9,5±0,22 months among urban population and 10,8 ± 0,29 months among rural population (p <0,01); in the RI these figures were - 8,5±0,26 months and 8,7±0,20 months, respectively (p >0,05). Up till the age of 6 months 17,6% of urban infants and 36,8% of rural infants of the CR (p <0,001) and 19,1% of urban and 19,7% of rural infants in the RI (p >0,05) received exclusive breast-feeding. It was established, that duration of the breast-feeding was influenced by the mothers' attitude to the issue or the dominant mothers' ideology, as well as by the duration of the only breast-feeding itself. Besides, prolongation of the breast-feeding period is contributed by introduction of the modern medico-organizational measures aimed at support and maintenance of the breast-feeding. Conclusions: complex medical and social research allowed to assess prevalence and duration of the breast-feeding in the CR and the RI, in accordance to modern recommendations of the WHO experts. The main social and medico-organizational factors and predictors of the breast-feeding long duration and the exclusive breast-feeding were revealed.